Piezoelectric film for underwater sound wave detection and preparation method and application thereof
By introducing zinc sulfide nanoparticles into poly(vinylidene fluoride-trifluoroethylene), the β-phase content and crystallization state are improved, and the problem of poor detection sensitivity of polyvinylidene fluoride piezoelectric materials is solved, achieving high sensitivity and uniformity The composite piezoelectric film is suitable for underwater acoustic wave detection.
Patent Information
- Application Number
- CN202411337827.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-17
AI Technical Summary
The low β-phase content of polyvinylidene fluoride organic piezoelectric materials leads to poor detection sensitivity. The uneven size of traditional inorganic nanofillers leads to uneven performance of composite piezoelectric films.
Zinc sulfide nanoparticles are used as inorganic nanofillers and copolymerized with poly(vinylidene fluoride-trifluoroethylene). Through the negative charge and surface convex structure of zinc sulfide, the β-phase content and crystallization state are improved, stress transmission is optimized, and uniform size is prepared. The nano zinc sulfide spheres are compounded with the polymer to form a piezoelectric film with high sensitivity.
The β-phase content and piezoelectric properties of the composite piezoelectric film are significantly improved, the detection sensitivity is enhanced, and the uniformity of the composite film's performance and the applicability of industrial production are ensured.
Smart Images

Figure CN119144027A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite voltage materials, and in particular to a piezoelectric film for underwater sound wave detection, and a preparation method and application thereof. Background Art
[0002] Polyvinylidene fluoride (PVDF) organic piezoelectric materials can realize the mutual conversion between mechanical energy and electrical energy, and are widely used in energy storage, driving and dynamic monitoring. Compared with traditional inorganic piezoelectric materials, PVDF is light and easy to conform to, and has a wide range of applications in human motion monitoring and medical diagnosis. In addition, PVDF is particularly suitable for electroacoustic materials due to its good frequency response performance, and has unique advantages in microphones, hydrophones, etc.
[0003] As a semi-crystalline polymer, PVDF has five conformations: α, β, γ, ε, and δ. The most common of the five conformations is the α phase with TGTG', which is the most stable at room temperature. However, due to the antiparallel stacking of dipoles, the α phase does not have piezoelectric properties. Compared with the α phase, the fluorine atoms and hydrogen atoms of the β phase are arranged in a TTTT all-trans conformation, and the direction of the dipole is orthogonal to the molecular chain axis. It is the crystalline phase with the largest polarization. Therefore, the content of the β crystal directly determines the strength of the piezoelectric properties of the PVDF film. The higher the content of the β crystal, the better the piezoelectric properties of the PVDF film. Therefore, increasing the content of the β phase is an effective way to enhance the piezoelectric properties of PVDF.
[0004] There are two methods to increase the β-phase content of PVDF film: chemical modification and physical modification. The chemical modification method is to introduce trifluoroethylene polar groups into the vinylidene fluoride chain to form poly(vinylidene fluoride-trifluoroethylene). The β-phase content in poly(vinylidene fluoride-trifluoroethylene) is significantly better than that in polyvinylidene fluoride. The physical modification method mainly includes mechanical stretching, electric polarization, adding fillers and annealing. Compared with the other three methods, the method of adding nanofillers to improve the β-phase has the advantages of simple operation and strong designability. By adjusting the shape, size and surface charge of the filler, it can better induce the generation of the β-phase.
[0005] In the process of mechanical-electrical energy conversion, in addition to the β phase, the efficiency of force transmission in the polymer will be another physical factor that determines the piezoelectric performance. Due to the flexibility of the polymer itself, the force transmission in the polymer will undergo a large degree of relaxation. The addition of nanofillers will optimize the force transmission in the flexible polymer, reduce the attenuation of the force, and allow more forces to participate in the energy conversion process, which indirectly improves the performance of the piezoelectric material from another perspective. Therefore, adding nanofillers is an effective way to improve piezoelectric performance.
[0006] However, traditional inorganic nanofillers often have large differences in specifications and sizes, which have a certain impact on the transmission of force and lead to uneven performance of composite piezoelectric films. The present invention successfully prepares nanofillers with uniform size and morphology through a simple one-pot method, and composites them with piezoelectric polymers to effectively improve the piezoelectric properties of composite piezoelectric films. Summary of the invention
[0007] The purpose of the present invention is to provide a piezoelectric film for underwater sound wave detection and its preparation method and application, so as to solve the problem that the β-phase content of poly(vinylidene fluoride) organic piezoelectric material is low and the detection sensitivity is poor. The present invention prepares a zinc sulfide-doped poly(vinylidene fluoride-trifluoroethylene) composite piezoelectric film and makes it into a hydrophone for underwater sound wave detection. The negative charge on the surface of nano zinc sulfide can interact with -CH2 in poly(vinylidene fluoride-trifluoroethylene), so that the polymer chain arrangement is more regular and more β-phase is generated. At the same time, when the zinc sulfide with a convex structure on the surface is subjected to external pressure, it can produce more contact sites for the piezoelectric material, so that the poly(vinylidene fluoride-trifluoroethylene) piezoelectric film produces a greater deformation, and the performance of the composite piezoelectric film is improved by improving the crystallization state and optimizing stress transfer.
[0008] To achieve the above object, the first aspect of the present invention provides a method for preparing a piezoelectric film for underwater acoustic wave detection, comprising the following steps: (1) mixing a sulfur source, a zinc source and a dispersant, then heating and stirring, centrifuging, drying and grinding to obtain nano zinc sulfide beads; (2) Ultrasonic dispersion of the obtained nano zinc sulfide spheres in an organic solvent to obtain a dispersion, poly (vinylidene fluoride-trifluoroethylene) is added to the dispersion, heated and stirred, and after stirring evenly, poured onto the prepared glass plate, naturally leveled, and then placed in an oven for drying to obtain a piezoelectric film.
[0009] Preferably, in step (1), the molar ratio of the sulfur source, the zinc source and the dispersant is 1:(2-3):(1-2). More preferably, the molar ratio of the sulfur source, the zinc source and the dispersant is 1:2.2:1.5.
[0010] Preferably, the sulfur source in step (1) is at least one of thioacetamide, sodium sulfide, and thiourea; the zinc source is at least one of zinc nitrate hexahydrate, zinc acetate, and zinc chloride; and the dispersant is at least one of polyvinyl pyrrolidone, sodium dodecyl sulfate, and polyacrylamide. More preferably, the sulfur source is thioacetamide, the zinc source is zinc nitrate hexahydrate, and the dispersant is polyvinyl pyrrolidone.
[0011] Preferably, in step (1), the heating temperature is 50-80°C, the stirring speed is 200-400 r / min, the heating time is 4-8 h, the centrifugal speed is 5000-10000 r / min, and the drying temperature is 55-65°C. More preferably, the heating temperature is 70°C, the stirring speed is 280 r / min, and the heating reaction time is 6 h.
[0012] Preferably, the mass fraction of the nano zinc sulfide beads added in step (2) is 1% to 3%, and the organic solvent is one of N,N-dimethylformamide, N-methylpyrrolidone, and N,N-dimethylacetamide.
[0013] Preferably, in step (2), the ultrasonic frequency is 20-200 kHz, and the ultrasonic power is 1-500 W.
[0014] Preferably, the mass fraction of poly(vinylidene fluoride-trifluoroethylene) in step (2) is 5% to 15%.
[0015] Preferably, the mass fraction of poly(vinylidene fluoride-trifluoroethylene) is 5%, 10%, 15%, respectively. More preferably, the mass fraction of poly(vinylidene fluoride-trifluoroethylene) is 10%.
[0016] Preferably, poly(vinylidene fluoride-trifluoroethylene) is a copolymer of vinylidene fluoride and trifluoroethylene, wherein the content of trifluoroethylene is not less than 20%. More preferably, the content of trifluoroethylene is 30%. Poly(vinylidene fluoride-trifluoroethylene) was purchased from Piezotech FC.
[0017] Preferably, in step (2), the heating temperature is 30-60°C, the heating time is 3-6 h, the drying temperature is 80-120°C, and the drying time is 2-3 h. More preferably, the mass fraction of zinc sulfide is 2%, the mass fraction of poly(vinylidene fluoride-trifluoroethylene) is 10%, the heating temperature is 50°C, the heating time is 5 h, the drying temperature is 100°C, and the drying time is 2.5 h.
[0018] A second aspect of the present invention provides a piezoelectric film for underwater acoustic wave detection, which is prepared by the above preparation method, and the thickness of the piezoelectric film is 30-50 μm.
[0019] A third aspect of the present invention provides a hydrophone for underwater sound wave detection, comprising a composite piezoelectric film, a positive electrode, a negative electrode, a PMMA shell and a submarine cable, wherein the composite piezoelectric film is the piezoelectric film prepared as described above.
[0020] Preferably, the positive electrode and the negative electrode are both gold electrodes plated by magnetron sputtering, and the electrode thickness is about 20 nm.
[0021] Preferably, the hydrophone is one or more of a cylindrical hydrophone, a membrane hydrophone, and a needle hydrophone.
[0022] Therefore, the present invention adopts a piezoelectric film for underwater acoustic wave detection with the above structure and a preparation method and application thereof, which have the following beneficial effects: (1) The piezoelectric film material of the present invention comprises poly(vinylidene fluoride-trifluoroethylene) and nano zinc sulfide beads, with poly(vinylidene fluoride-trifluoroethylene) as a substrate and nano zinc sulfide beads as inorganic nano fillers uniformly distributed in the polymer substrate. Through the combination of the two, the obtained composite piezoelectric film has high sensitivity and is suitable for underwater sound wave detection.
[0023] (2) The present invention improves the crystal state of poly(vinylidene fluoride-trifluoroethylene) by controlling the amount of zinc sulfide added. The nano zinc sulfide with a rough surface and negative charge acts as a crystallization site, thereby improving the crystallinity of poly(vinylidene fluoride-trifluoroethylene). Through the interaction with carbon-hydrogen dipoles, the crystal phase in poly(vinylidene fluoride-trifluoroethylene) tends to be more in the all-trans β phase.
[0024] (3) The present invention uses the synergistic effect of piezoelectric effect and stress transfer, combined with a solution casting preparation process, to obtain a composite piezoelectric film with excellent piezoelectric properties that can be prepared on a large area. The preparation process is easy to operate and has simple process steps, making it suitable for industrial production applications.
[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron micrograph of the one-pot synthesis of uniform-sized zinc sulfide nanoparticles; Figure 2 A physical picture of the composite piezoelectric film prepared in Example 2; Figure 3 A diagram showing the mechanism of energy conversion by the composite piezoelectric film of the present invention; Figure 4 This is a scanning electron microscope image of the composite piezoelectric film prepared in Example 2; Figure 5 The Fourier transform infrared spectra of the composite piezoelectric films doped with different contents of zinc sulfide in the present invention and the β-phase content diagram obtained by calculation, wherein: ▲ represents poly(vinylidene fluoride-trifluoroethylene) not doped with zinc sulfide, ◆ represents poly(vinylidene fluoride-trifluoroethylene) composited with 1% zinc sulfide, ■ represents composited with 2% zinc sulfide; ● represents composited with 3% zinc sulfide; Figure 6 A physical picture of a hydrophone made of the composite piezoelectric film prepared in Example 2; Figure 7 This is a test diagram of underwater sound wave detection by a hydrophone made of the composite piezoelectric film prepared in Example 2; Figure 8 This is a graph showing the frequency variation over time of a hydrophone made of the composite piezoelectric film prepared in Example 2 for underwater sound wave detection. DETAILED DESCRIPTION
[0027] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.
[0028] Example 1 A method for preparing a piezoelectric film for underwater acoustic wave detection comprises the following steps: (1) Soak the glass substrate in a mixed solution of concentrated sulfuric acid and concentrated nitric acid (volume ratio 7:3), heat it at 100°C, and when no bubbles emerge from the mixed solution, take out the glass substrate, rinse it three times with anhydrous ethanol to remove the residual acid solution, and then ultrasonically clean it three times with anhydrous ethanol / acetone (volume ratio 1:1) mixed solution. Soak the cleaned glass substrate in anhydrous ethanol and blow it dry with inert gas before use to obtain a clean glass substrate; (2) Disperse 6 g of polyvinyl pyrrolidone in 200 mL of deionized water. After the dispersion is uniform, add 4 g of thioacetamide, 6 g of zinc nitrate hexahydrate, and 20 μL of concentrated nitric acid. React at 70°C and 300 r / min for 7 h. Wash the white emulsion after the reaction by centrifugation with deionized water several times. Dry the zinc sulfide obtained by centrifugation in an oven at 60°C for 24 h to obtain nano zinc sulfide pellets. The size of the nano zinc sulfide spheres is 220 nm, and the surface has protrusions. The small size helps to act as a crystal nucleus and promote the formation of a crystalline phase. The protrusions on the surface are more likely to produce stress concentration, which is beneficial to the improvement of sensitivity. Under the action of polyvinyl pyrrolidone, the negative charge on the surface helps to interact with the -CH2 dipole in PVDF-TrFE to produce more β phases. At the same time, zinc sulfide itself, as an inorganic piezoelectric material, has a synergistic effect on the improvement of the piezoelectric effect of the composite film.
[0029] (3) Add zinc sulfide nanospheres into DMF, disperse them ultrasonically for 30 min, stir them magnetically at 50 °C for 20 min, add poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) powder, and continue stirring at 50 °C for 5 h to obtain a suspension; the mass fractions of zinc sulfide nanospheres and PVDF in the suspension are 1% and 10%, respectively; (4) Take 0.4 g of the suspension obtained in step (3) and spread it on the glass substrate obtained in step (1). After it is naturally leveled on the glass substrate, place it in a vacuum oven at 100° C. and dry it for 2.5 hours to obtain the piezoelectric film.
[0030] Example 2 A piezoelectric film for underwater acoustic wave detection, which differs from Example 1 only in that the mass fraction of zinc sulfide in the suspension in step (3) is 2%, and other substances and preparation methods are the same as those in Example 1.
[0031] Example 3 A piezoelectric film for underwater acoustic wave detection, which differs from Example 1 only in that the mass fraction of zinc sulfide in the suspension in step (3) is 3%, and other substances and preparation methods are the same as those in Example 1.
[0032] Comparative Example 1 A PVDF-TrFE piezoelectric film, the preparation method of which comprises the following steps: (1) Soak the glass substrate in a mixed solution of concentrated sulfuric acid and concentrated nitric acid (volume ratio 7:3), heat it at 100°C, and when no bubbles emerge from the mixed solution, take out the glass substrate, rinse it three times with anhydrous ethanol to remove the residual acid solution, and then ultrasonically clean it three times with anhydrous ethanol / acetone (volume ratio 1:1) mixed solution. Soak the cleaned glass substrate in anhydrous ethanol and blow it dry with inert gas before use to obtain a clean glass substrate; (2) Add PVDF-TrFE to DMF and stir magnetically at 50 °C for 5 h to obtain a solution with a PVDF-TrFE mass fraction of 10%; (3) Take 0.4 g of the suspension obtained in step (3) and spread it evenly on the glass substrate obtained in step (1). After it is naturally leveled on the glass substrate, place it in a vacuum oven at 100° C. and dry it for 2.5 h to obtain a piezoelectric film.
[0033] Basic performance test of piezoelectric film Figure 1 This is a scanning electron microscopy image of zinc sulfide nanoparticles prepared by the one-pot method, which confirms that the synthesized zinc sulfide is a uniform nanoparticle with a size of 220 nm and protrusions on the surface.
[0034] Figure 2 This is a physical picture of the composite piezoelectric film doped with zinc sulfide nanoparticles. The composite film is translucent, with a thickness of 40 μm and high flexibility.
[0035] Figure 3This is the working mechanism diagram of the composite piezoelectric film. On the one hand, the nano-zinc sulfide spheres can act as nucleating agents to promote the crystallization of poly(vinylidene fluoride-trifluoroethylene). On the other hand, due to the negative charge on the surface of the nano-zinc sulfide spheres, they can interact with the -CH2 dipole in poly(vinylidene fluoride-trifluoroethylene), prompting the polymer chains to have a more regular arrangement, thereby increasing the β phase content, which is beneficial to the improvement of piezoelectric performance. When the piezoelectric film is not stimulated by the outside world, the positive and negative charge centers coincide and the film does not show any electrical properties to the outside. When an external force acts on the piezoelectric film, the presence of the nano-zinc sulfide spheres will better transmit this stress to the piezoelectric polymer. At this time, with the change of the dipole moment, the positive and negative charge centers separate, thereby generating an instantaneous electric potential and realizing the conversion of mechanical energy into electrical energy.
[0036] Figure 4 This is a scanning electron microscope image of a composite piezoelectric film doped with zinc sulfide nanoparticles. The nano zinc sulfide spheres are evenly dispersed in poly(vinylidene fluoride-trifluoroethylene), and the crystal orientation of poly(vinylidene fluoride-trifluoroethylene) can be clearly seen.
[0037] Figure 5 Fourier transform infrared spectra of composite piezoelectric films doped with different contents of zinc sulfide and poly (vinylidene fluoride-trifluoroethylene) piezoelectric films without zinc sulfide doping as a comparison, and the formula F(β)=A β / (1.26A α +A β ) The content of β phase in different piezoelectric films, A α, A β They correspond to the intensities at 763 and 842 wavenumbers in the infrared absorption spectrum. Figure 5 It can be seen that the β-phase content of the composite piezoelectric films obtained in Example 1, Example 2 and Example 3 is significantly higher than that of the piezoelectric film not doped with zinc sulfide in Comparative Example 1. This further illustrates that the nano zinc sulfide spheres play a role in increasing the β-phase content in the composite piezoelectric film.
[0038] Figure 6 The hydrophone made by using the composite piezoelectric film in Example 2 mainly comprises four parts: a composite piezoelectric film, a metal electrode, a PMMA shell and a submarine cable.
[0039] Figure 7 and Figure 8 In order to use the hydrophone made of the composite piezoelectric film in Example 2 to detect sound waves in natural water conditions, the signal of the model ship traveling above the lake surface can be captured more accurately, and the spectrum analysis can be performed on it, and the running posture of the model ship can be obtained through analysis. It can be seen that the zinc sulfide and poly (vinylidene fluoride-trifluoroethylene) composite piezoelectric film prepared by the present invention has a high β phase and excellent sensitivity, and can be used for underwater sound wave detection.
[0040] Therefore, the present invention adopts a piezoelectric film for underwater sound wave detection with the above structure, and its preparation method and application. The piezoelectric film material includes poly (vinylidene fluoride-trifluoroethylene) and zinc sulfide nanoparticles. The poly (vinylidene fluoride-trifluoroethylene) is used as a matrix and filled with zinc sulfide particles, which not only effectively solves the disadvantage of force transmission relaxation in polymer materials, but also effectively improves the piezoelectric properties of the composite piezoelectric film itself, affects the β phase of poly (vinylidene fluoride-trifluoroethylene), and further improves the sensitivity and stability of the composite piezoelectric film; by combining poly (vinylidene fluoride-trifluoroethylene) and zinc sulfide particles, the two are coordinated to obtain a composite piezoelectric film with excellent sensitivity and high-efficiency force-to-electricity conversion, which has excellent mechanical properties, is non-toxic and pollution-free, and is suitable for use in underwater sound wave detection.
[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a piezoelectric film for underwater acoustic wave detection, It is characterized in that The following steps are involved: (1) mixing a sulfur source, a zinc source and a dispersant, then heating and stirring, centrifuging, drying and grinding to obtain nano zinc sulfide beads; (2) Ultrasonic dispersion of the obtained nano zinc sulfide spheres in an organic solvent to obtain a dispersion, poly (vinylidene fluoride-trifluoroethylene) is added to the dispersion, heated and stirred, and after stirring evenly, poured onto the prepared glass plate, naturally leveled, and then placed in an oven for drying to obtain a piezoelectric film.
2. A method for preparing a piezoelectric film for underwater acoustic wave detection according to claim 1, It is characterized in that In step (1), the molar ratio of the sulfur source, the zinc source and the dispersant is 1:(2-3):(1-2).
3. The method for preparing a piezoelectric film for underwater acoustic wave detection according to claim 1, It is characterized in that The sulfur source in step (1) is at least one of thioacetamide, sodium sulfide, and thiourea; the zinc source is at least one of zinc nitrate hexahydrate, zinc acetate, and zinc chloride; and the dispersant is at least one of polyvinyl pyrrolidone, sodium dodecyl sulfate, and polyacrylamide.
4. The method for preparing a piezoelectric film for underwater acoustic wave detection according to claim 1, It is characterized in that In step (1), the heating temperature is 50-80°C, the stirring speed is 200-400 r / min, the heating time is 4-8 h, the centrifugal speed is 5000-10000 r / min, and the drying temperature is 55-65°C.
5. The method for preparing a piezoelectric film for underwater acoustic wave detection according to claim 1, It is characterized in that The mass fraction of the nano zinc sulfide beads added in step (2) is 1% to 3%, and the organic solvent is one of N,N-dimethylformamide, N-methylpyrrolidone, and N,N-dimethylacetamide.
6. The method for preparing a piezoelectric film for underwater acoustic wave detection according to claim 1, It is characterized in that In step (2), the ultrasonic frequency is 20-200 KHz, and the ultrasonic power is 1-500 W.
7. The method for preparing a piezoelectric film for underwater acoustic wave detection according to claim 1, It is characterized in that The mass fraction of poly(vinylidene fluoride-trifluoroethylene) in step (2) is 5% to 15%.
8. The method for preparing a piezoelectric film for underwater acoustic wave detection according to claim 1, It is characterized in that In step (2), the heating temperature is 30-60°C, the heating time is 3-6 h, the drying temperature is 80-120°C, and the drying time is 2-3 h.
9. A piezoelectric film for underwater acoustic wave detection, It is characterized in that The piezoelectric film is prepared by the preparation method according to any one of claims 1 to 8, and the thickness of the piezoelectric film is 30 to 50 μm.
10. A hydrophone for underwater sound wave detection, comprising a composite piezoelectric film, a positive electrode, a negative electrode, a PMMA shell and a submarine cable, It is characterized in that The composite piezoelectric film adopts the piezoelectric film according to claim 9.
Citation Information
Cited By
Electric response nanofiber composite membrane as well as preparation method and application thereof
CN122629663A
